(untitled) (Hekima Review, 1993)
For a long time in life of the church, evangelisation was mostly understood as the task to bring the good news of Jesus Christ to the Pagans in mission countries in order to convert them. This idea marked the activity of the church whose traditional mission was carried out in centuries by generous missionaries coming from Europe to the third world.